PEMBELAJARAN INOVATIF BAHASA INDONESIA: IMPLEMENTASI STRATEGI PENGEMBANGAN PARAGRAF DAN TANYA JAWAB ANTARSISWA - Nasucha, Yakub; Huda, Miftakhul; Santoso, Tri; Ihsanudin, Muh (WARTA, 2015)
Many Indonesian teachers of Senior High School have used a lecturing method. Indonesian learning, it is necessary for them to implement an appropriate method and have a high creativity as well as make innovation. For them, a cooperative-based learning innovation is considered difficult and costly. Therefore, they remain to implement a lecturing method. The problems are that a cooperative-based learning has seldom been implemented and they have frequently used a lecturing method. In Indonesian learning, thus, it is necessary to implement a new strategy, called paragraph development and questions-answers between students. The strategy makes the students active, creative, and pleasurable because it focuses on cooperation in its implementation.